Learning to teach in a full-service school through a self-study - Zondo, Cebolakhe (My University, 2019)
This self-study in which I investigated how to teach Natural Sciences and Mathematics in a Full-Service school (FSS) was motivated by the realisation that the Initial Teacher Education training that I received never prepared me for teaching at such a school. The aim of this study was therefore, to document my experiences of teaching at a FSS as a novice educator with the primary goal of sharing what I have come to learn and the kind of knowledge that one requires to teach in a FSS. Being a self-study, I was the main participant. My Grade 4, 6 and 7 learners became participants by being in the classes that I was teaching. In the study, I employed three ways of data collection: journal entries of trigger incidents, transcribed recordings of discussions held with critical friends and my reflections that followed each discussion. All data collected was in text form. Inductive coding was used to create meaning of what I was experiencing. This study produced two key findings about learners and about teaching in a FSS. The first finding is that most learners in Full-Service School are bodily-kinesthetic i.e. they learn best when they use their bodies and through movements. The second finding is that learners in a FSS are very slow to grasp concepts. Therefore, it is very important for the teachers in FSSs to consider the slow pace of the learners, even though CAPS propose specific content and timelines. These two findings highlight two pieces of knowledge about learners and about teaching in a FSS (that I was not aware of as a newly qualified teacher) that any new educator should be aware of and be trained to deal with. This study therefore, recommends that teacher training institutions must incorporate modules in their teacher preparation programs that prepare new educators specifically for teaching in a FSSs. In addition to the findings above, this study demonstrated that self-study is a very good research methodology that can be used to develop effective teaching practices as it can help teachers to make sense of their own teaching practices and how those experiences can be used to promote better teaching and learning in future.
A thesis submitted to the Wits School of Education, Faculty of Humanities, the University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Education in Science Education, Johannesburg 2019
Keywords: Teachers--Training of; Educational technology